Development of a STEM-based e-module using the MIKiR model on energy sources material to enhance students’ critical thinking skills - Alim, Jesi Alexander; Hermita, Neni; Putra, Zetra Hainul; Oktaviani, Cici (Frontiers in Education, 2025)
IntroductionElementary students’ critical thinking skills remain below average, partly due to the lack of interactive teaching materials. This research aims to develop STEM-integrated MIKiR-based e-modules on the topic of energy sources for fourth-grade students that are valid, practical, and effective.MethodsThe study uses the Plomp development model consisting of Preliminary Research, Prototyping, and Assessment phases. Participants included 2 expert lecturers, 2 teachers, and 69 fourth-grade students. Data were collected through questionnaires, interviews, and tests, and analyzed using descriptive quantitative methods.ResultsMedia expert validation scored 97.03%, and language experts 90%, indicating high validity. The practicality score was 96.33%. A t-test result of 0.001 < 0.005 shows a significant effect after implementation.DiscussionThe STEM-based MIKiR e-modules effectively improve students’ critical thinking skills and can be used as innovative and interactive teaching materials.